Effect of pH, milling time, and Isobam content on porous silicon nitride ceramics prepared by gel casting - Hailing Yang; Zhi Wang; Mengyong Sun; Fei Chen; Jun Ji; Sique Chen; Yingying Chen; Deli Ma; Zhenyu Zhang; Baocai Pan; Yulin Wei; Qinggang Li (Advanced Powder Materials, 2023)
As a non-toxic copolymer of isobutylene and maleic anhydride, Isobam is successfully used as a dispersant and a gelling agent for fabricating porous Si3N4 ceramics by gel casting. The dispersity and rheological properties of the Si3N4 slurry are influenced by the pH, milling time, and Isobam content which varies from 0.1 ​wt.% to 0.6 ​wt.%, and these factors are investigated. The slurry with 40 ​vol.% solid content and milled for 4 ​h has a high zeta potential at pH 12 (adjusted by Tetramethyl ammonium hydroxide (TMAH)), which means that the particles are well dispersed. The mechanisms of TMAH are electrostatic repulsion and steric hindrance. The viscosity of the slurry increases with the increase of Isobam content. After pressureless sintering at 1700 ​°C for 2 ​h, a uniform unique interlocking microstructure of rod-like β-Si3N4 grains is observed, which may improve the flexural strength of the ceramics by intergranular fracture and particle pullout of β-Si3N4 grains. The density and porosity of the samples fluctuate negligibly with the increase of Isobam content, and the Si3N4 ceramic with 0.1 ​wt.% Isobam exhibits the highest bending strength of 251.6 ​MPa among all samples.